Chemical composition and in vitro digestibility of herbaceous autochthonous plants in a semi-arid region of Spain - Muñoz F.; Andueza D.; Delgado I.; Ochoa M.J. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Chemical composition and in vitro dry matter digestibility of herbaceous plants were estimated in four seasons and four localities in a semiarid region of Spain. The plants were: Dactylis glomerata, Plantago albicans, Brachypodium retusum, Stipa sp., Lygeum spartum. The results showed significant differences between species and seasons for all parameters studied.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)